Discussion to the special issue: Supporting the transition of a diversity of students: Developing the "whole student" during and beyond their time at higher education - Jacques van der Meer (EARLI, 2021)
Apart from the current Covid19 context, the higher education sectors across the world have been faced with major challenges over the last few decades (Auerbach et al., 2018; Haggis, 2004), including increased numbers and diversity. Considering the many challenges in higher education, especially the rise of students' mental health issues, I am strongly convinced that education sectors, but in particular the higher education sector, have a societal responsibility to not just focus on students as learners of knowledge and/or professional skills, but to support them in being developed as "whole students". All these challenges also raise a need for research into the broader context to identify how we can better support the diverse student population as they transition into higher education, but also how to prepare them for a positive experience during and beyond their time in higher education. Overall, it can be said that the contributions to this special issue beneficially addressed some of the main foci to widening the perspectives on diversity related to the transition into higher education. The contribution came from different European countries, including Belgium, Germany, Italy, Sweden, Switzerland, The Netherlands and the United Kingdom. De Clercq et al. (in this special issue) indicated that environmental characteristics, such as distinctiveness of countries, is often overlooked in research. In this discussion article, therefore, some particular references will also be made to a specific country, New Zealand. This may be of interest and relevant for the particular questions raised in this special issue as focusing on student diversity in educational contexts has been considered important for some time in this country. Aoteraroa New Zealand is a country in the South Pacific colonised by Europeans in the 19th century. In the second part of the 20th century, the focus across the New Zealand education sectors, including higher education, started to develop beyond just a European perspective, and started to focus more on recognition of student diversity. Initially, the main focus was on the indigenous population, the Māori people. In the last few decades of the 20th century, the focus was extended to the Pacific Island people, many of whom migrated to New Zealand from a wide range of different islands in the South Pacific. In the 21st century, the focus on Culturally and Linguistically Diverse (CALD) groups was further extended, and over the last decade also because of the increase of refugees from the Middle East and Asia. Providing some insights from the other end of the world, in quite a different and de-colonised ex-European nation may help European (and other) countries to reflect on their own approaches.